2006
DOI: 10.1215/15228517-2005-006
|View full text |Cite
|
Sign up to set email alerts
|

Expression studies in gliomas and glial cells do not support a tumor suppressor role for LGI11

Abstract: Disruptions of LGI1 in glioblastoma (GBM) cell lines and LGI1 mutations in families with autosomal dominant epilepsy imply a role for LGI1 in glial cells as well as in neurons. Although we and others could not find LGI1 mutations in malignant gliomas, our initial studies appeared to support the idea that LGI1 is poorly expressed or absent in these tumors. Microarray data suggested that LGI1 could be involved in the control of matrix metalloproteinases, and we found that tumors derived from U87 glioblastoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
13
0
4
Order By: Relevance
“…An alternative functional hypothesis postulates a role for LGI1 in brain development, as suggested by its expression in the developing mouse brain [Piepoli et al, 2006;Ribeiro et al, 2008] and by the structural homology of the LRR region with that of other LRR proteins essential for the development of the central nervous system, such as slit, tartan, and toll [Cowell, 2002]. This hypothesis has recently received support by in vitro experiments showing that LGI1 is involved in the control of proliferation and survival of neuroblastoma cell lines [Gabellini et al, 2006].…”
Section: It Is Not Yet Clear Whethermentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative functional hypothesis postulates a role for LGI1 in brain development, as suggested by its expression in the developing mouse brain [Piepoli et al, 2006;Ribeiro et al, 2008] and by the structural homology of the LRR region with that of other LRR proteins essential for the development of the central nervous system, such as slit, tartan, and toll [Cowell, 2002]. This hypothesis has recently received support by in vitro experiments showing that LGI1 is involved in the control of proliferation and survival of neuroblastoma cell lines [Gabellini et al, 2006].…”
Section: It Is Not Yet Clear Whethermentioning
confidence: 99%
“…However, neither point mutations affecting the LGI1 coding sequence nor differential methylation of its core promoter region could be demonstrated in these tumors, arguing against a role of LGI1 as a tumor suppressor gene [Krex et al, 2002;Piepoli et al, 2006;Somerville et al, 2000]. Recent studies have implicated LGI1 in the control of proliferation and invasiveness of glioma cell lines [Kunapuli et al, 2003].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous low-resolution immunohistochemical studies Piepoli et al 2006) showed the presence of the Lgi1 protein in neurons, but little information could be soma (a, b), Lgi1 molecules occurs on rough endoplasmic reticulum (arrows), on Golgi complexes (G) and free in the cytoplasm (thin arrows), while in axons (c) they appear to be preferentially associated with neurotubules and neuroWlaments (arrowheads). No signal is present at synapses (asterisk).…”
Section: Discussionmentioning
confidence: 99%
“…In low-resolution immunohistochemical studies Piepoli et al 2006), the Lgi1 protein was found to be predominantly expressed in neurons. Schulte et al (2006) provided evidence that the Lgi1 protein is associated with the presynaptic, rapidly inactivating Kv1 potassium channel suggesting its involvement in the control of inactivation of this channel; Fukata et al (2006) showed that Lgi1 selectively binds to ADAM22, a postsynaptic membrane receptor protein, thereby potentiating synaptic alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid currents in hippocampal slices.…”
Section: Introductionmentioning
confidence: 97%